Novel tyrosinase inhibitory peptide with free radical scavenging ability - Zhiwei Shen; Yujiao Wang; Zhen Guo; Tingyuan Tan; Yi Zhang (Taylor & Francis Group, 2019)
Tyrosinase is a key enzyme involved in melanin synthesis. Therefore, various tyrosinase inhibitors have been screened by researchers in recent years. In the present study, we discovered a novel tyrosinase inhibitor, a peptide ECGYF (named EF-5), with free radical scavenging ability. The effect of tyrosinase inhibition by EF-5 was stronger than that of arbutin and glutathione, when analyzed both in vitro (IC50: 0.46 mM) and in vivo. The UV-Vis absorption and circular dichroism spectroscopies indicated that EF-5 interacted with tyrosinase in a different way as that of glutathione. The results of molecular docking showed that the binding between EF-5 and tyrosinase was determined majorly by hydrogen bonds and hydrophobic interactions. EF-5 had also retained its ability to scavenge both hydroxyl and superoxide radicals in vitro and was found to be nontoxic to cells, as revealed by the MTT assay. These features suggested that the EF-5 peptide may serve as a safe and effective alternative as a tyrosinase inhibitor.